Autoimmune psychosis: an international consensus on an approach to the diagnosis and management of psychosis of suspected autoimmune origin. (January 2020) - Pollak, Thomas A; Lennox, Belinda R; Müller, Sabine; Benros, Michael E; Prüss, Harald; Tebartz van Elst, Ludger; Klein, Hans; Steiner, Johann; Frodl, Thomas; Bogerts, Bernhard; Tian, Li; Groc, Laurent; et al.
Summary: There is increasing recognition in the neurological and psychiatric literature of patients with so-called isolated psychotic presentations (ie, with no, or minimal, neurological features) who have tested positive for neuronal autoantibodies (principally N-methyl-D-aspartate receptor antibodies) and who have responded to immunotherapies. Although these individuals are sometimes described as having atypical, mild, or attenuated forms of autoimmune encephalitis, some authors feel that that these cases are sufficiently different from typical autoimmune encephalitis to establish a new category of so-called autoimmune psychosis. We briefly review the background, discuss the existing evidence for a form of autoimmune psychosis, and propose a novel, conservative approach to the recognition of possible, probable, and definite autoimmune psychoses for use in psychiatric practice. We also outline the investigations required and the appropriate therapeutic approaches, both psychiatric and immunological, for probable and definite cases of autoimmune psychoses, and discuss the ethical issues posed by this challenging diagnostic category.